DESCRIPTION OF THE SMALL SEINER FLEET IN THE JAVA SEA - Ecoutin J.M; Suherman Banon Atmaja; Pottier M; Wijopriono Wijopriono (Indonesian Fisheries Research Journal, 1997)
Several census of fhe fishing units using mini seine nets were carried out in 1994 and1995. The first census, in October 1994, set the inquiry protocol.